Processes of spatial concentration and specialisation of industry by the intensity of R&D work in the Lower Silesian Voivodeship (Poland) - Brezdeń, Paweł; Sikorski, Dominik (Quaestiones Geographicae, 2023)
The aim of this article is to assess the spatial diversity and to identify the spatial distribution of industry, as well as the directions and scales of its transformations based on the processes of spatial concentration and specialisation of the industrial activity from the perspective of the intensity of research and development (R&D) work in the areas of the Lower Silesian Voivodeship. The analysis of the location of industrial activity was conducted based on the entities registered in section C (manufacturing) of the Polish Classification of Activity (PKD). Spatial structures of the industry innovation are presented by applying the classification of manufacturing concerning the intensity of R&D for high-technology, medium high-technology, medium low-technology and low-technology industries. The research was conducted for municipalities divided into cities and rural areas. The results indicate significant changes that took place in the years 2009–2020 in the spatial structure of the whole region, as well as in the urban spatial distribution due to the occurring processes of concentration and specialisation of industrial activity. These changes were simultaneously accompanied by the decreasing level of the concentration of industrial production. Additionally, the Lower Silesian Voivodeship is also characterised by significant spatial diversity of the concentration and specialisation processes of industrial activity. The identified regularities demonstrate the growing role of the suburban zones of large cities, which is particularly visible in the example of Wrocław, an area of intensive diffusion of industrial activity from the central hub. These processes also diffuse into smaller urban centres in the voivodeship.